Role of Growth Hormone/Insulin-Like Growth Factor-1 Axis Dysfunction and Inflammatory Cytokines in Pediatric Short Stature: - - Yang, Qingfu; Chen, Shanshan; Wu, Tieniu; Peng, Jingxin; Mao, Lidan (Journal of Medical Biochemistry, 2025)
Background: Pediatric short stature is a prevalent clinical issue, often linked to dysfunction in the growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis. Recent research suggests that inflammatory cytokines and serum markers may play a role in this dysfunction. This study aims to explore the molecular mechanisms contributing to GH/IGF-1 axis dysfunction, along with the levels of inflammatory cytokines and other relevant markers in children with short stature.Methods: 150 children diagnosed with short stature (defined as height below the 3rd percentile for age and sex) were recruited from the endocrinology ward of a tertiary care hospital. A control group of 150 age- and sex-matched healthy children was included for comparison. Serum levels of GH, IGF-1, interleukin-6 (IL-6), interleukin-8 (IL-8), and other relevant markers were measured using enzyme-linked immunosorbent assay (ELISA). Genetic analysis was performed to identify potential mutations in GH/IGF-1 axis-related genes. Data were analyzed using SPSS software, with statistical significance set at p < 0.05.Results: Children with short stature exhibited significantly lower serum levels of GH and IGF-1 compared to controls (p < 0.001). Elevated levels of IL-6 and IL-8 were found in the short stature group (p < 0.01). Genetic analysis revealed a higher frequency of mutations in the growth hormone receptor (GHR) gene in the short stature cohort. Correlation analysis showed a negative association between serum IL-6 levels and IGF-1 levels (r = -0.45, p < 0.001).Conclusion: This study provides evidence that dysfunction in the GH/IGF-1 axis, along with elevated inflammatory cytokines, may contribute to the pathogenesis of pediatric short stature. Further research is needed to investigate potential therapeutic targets and interventions aimed at addressing these molecular mechanisms.
Keywords: Pediatric short stature, GH/IGF-1 axis, inflammatory cytokines, interleukin-6, interleukin-8, genetic mutations, growth hormone receptor